T Tinjauan Etika Dalam Penerapan Sertifikat Tanah Elektronik - Martin, Elza Kamali; Hayat (LPPM STISIP IMAM BONJOL, 2025)
Electronic land certificates have revolutionized the way land ownership is recorded and verified. By digitizing these important documents, they have become more secure, accessible, and efficient. This is certainly a positive development in the implementation of land certification. Previously, there were shortcomings related to efficiency and data accuracy. However, every policy certainly needs an ethical review to evaluate and ensure that the policies implemented can run well and perfectly. The purpose of this study is to analyze the problems in the implementation of electronic land certification and explore ethical reviews in overcoming problems related to the implementation of electronic land certificates. Researchers use library research methods by critically and in-depth review of relevant library materials. This study raises several conclusions that the problems in land certification are related to data efficiency and accuracy, as well as fraud and data security. In addition, the steps and ethical considerations that need to be taken to resolve these problems are by ensuring data integrity and security, preventing fraud and data falsification, and implementing the principles of justice and transparency in making land certificates.